Pemetaan Jalur Evakuasi Tsunami Berbasis GIS Untuk Mendukung Edukasi Masyarakat Desa Balai Naras - Jonni Mardizal; Rino Wahyudi; Muhammad Afghan Arrazy; Zaskia Khairunnisa; Nikita Nalsy; Puja Enjelika Safitri (CV. ITTC INDONESIA, 2026)
Balai Naras Village, located in Pariaman Utara District, Pariaman City, West Sumatra, is a low-lying coastal area that faces the Indian Ocean and is at significant risk of tsunamis. A key problem identified during the KKN community service activity was the absence of a clear, systematic tsunami evacuation map accessible to the public. This activity aimed to: (1) map tsunami hazard zones using Geographic Information Systems (GIS); (2) design effective evacuation routes toward temporary evacuation points (TES); and (3) use the resulting map as an educational tool to improve community preparedness. Spatial analysis was conducted using ArcGIS through overlay and network analysis techniques, combining BMKG tsunami hazard data, road networks, river systems, and field observation data collected via GPS. The results show that the village is divided into two hazard zones: a high-alert zone (>3 meters) dominating the coastal area, and a warning zone (<3 meters) extending further inland. Two temporary evacuation points were identified: Mushalla Nurul Fajri and SDN 01 Balai Naras. The completed map was printed and installed on an information board in front of the village office. Community response was highly positive, demonstrating that the combination of GIS-based mapping and direct socialization is an effective approach to building tsunami preparedness in coastal villages.